IMPLEMENTASI KEBIJAKAN TENTANG PROGRAM BINA KELUARGA LANJUT USIA OLEH TENAGA PENYULUH KELUARGA BERENCANA DI DESA CIKUKULU TASIKMALAYA - Nunung, Adypia; Aditiyawarman; Garis, Regi Refian (Journal Education and Government Wiyata, 2023)
The results of the author's observations indicate that the implementation of the Policy on the Elderly Family Development Program by Family Planning Extension Workers in Cikukulu Village, Karangnunggal District, Tasikmalaya Regency is still not optimal. The purpose of this study was to determine the Implementation of Policies on the Elderly Family Development Program by Family Planning Extension Workers. The method used in this research is descriptive analysis. Informants as many as 10 people. Data collection techniques are library research, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through data processing from interviews and observations to draw conclusions so that they can answer problems in research. Based on the results of the study that: 1) Policy Implementation regarding the Elderly Family Development Program has not been carried out in accordance with several stages that must be carried out, which include the lack of availability of resources, both budgets, implementing resources and facilities and infrastructure. Likewise with the results of observations made it is known that Policy Implementation is not supported by an adequate budget, besides that officers have difficulty because not all facilities and infrastructure can be equipped. 2) There are obstacles, including the lack of availability of resources, both budgets, implementing resources and supporting facilities and infrastructure, besides that program socialization to the community is still lacking. Likewise, the observation results show that budget support is still lacking, besides that the existing facilities and infrastructure are inadequate to be able to implement the program as expected. 3) There are efforts to overcome obstacles, including providing resources, both budgets, implementing resources and supporting facilities and infrastructure besides conducting outreach to elderly families. Likewise, from the results of observations, it is known that there are efforts, including involving cadres in village deliberation activities, completing facilities and infrastructure in stages so that the program can be implemented according to expectation.